2014
DOI: 10.1016/j.jfineco.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Freedom of choice between unitary and two-tier boards: An empirical analysis

Abstract: We examine board structure in France, which since 1966 has allowed firms freedom to choose between unitary and two-tier boards. We analyze how this choice relates to characteristics of the firm and its environment. Firms with severe asymmetric information tend to opt for unitary boards; firms with a potential for private benefits extraction tend to adopt two-tier boards. There is enhanced sensitivity of CEO turnover to performance at firms with two-tier boards, indicating greater monitoring. Our results are br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 68 publications
0
43
0
15
Order By: Relevance
“…Belot et al . () hypothesized and found that the one‐tier board offers benefits in terms of mitigating information asymmetry problems, while a two‐tier board is more efficient for companies with high risks of managerial rent extractions, because this type of board limits discretion of management in the company. Given that both governance structures may have merits, we expected the value of firms to increase if this option becomes available to them, which we summarize in Hypothesis :Hypothesis (monism only/dualism only): Companies located in a country that allows only the one‐tier or two‐tier board structure under national corporate law will experience a positive abnormal return at the time when the first public information about the reincorporation leaks to the market .…”
Section: Regulation and Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Belot et al . () hypothesized and found that the one‐tier board offers benefits in terms of mitigating information asymmetry problems, while a two‐tier board is more efficient for companies with high risks of managerial rent extractions, because this type of board limits discretion of management in the company. Given that both governance structures may have merits, we expected the value of firms to increase if this option becomes available to them, which we summarize in Hypothesis :Hypothesis (monism only/dualism only): Companies located in a country that allows only the one‐tier or two‐tier board structure under national corporate law will experience a positive abnormal return at the time when the first public information about the reincorporation leaks to the market .…”
Section: Regulation and Hypothesesmentioning
confidence: 99%
“…As shown above, the SE regulation generally provides additional flexibility in corporate governance structures in some EU Member States. Belot et al (2014) hypothesized and found that the one-tier board offers benefits in terms of mitigating information asymmetry problems, while a two-tier board is more efficient for companies with high risks of managerial rent extractions, because this type of board limits discretion of management in the company. Given that both governance structures may have merits, we expected the value of firms to increase if this option becomes available to them, which we summarize in Hypothesis 1:…”
Section: Country-level Effectsmentioning
confidence: 99%
See 3 more Smart Citations